PENINGKATAN KUALITAS PENDIDIKAN DAN PEMBANGUNAN KULTUR GLOBAL - Umar, Jusnimar (Analisis: Jurnal Studi Keislaman, 2015)
THE QUALITY IMPROVEMENT OF EDUCATION AND DEVELOPMENT  OF GLOBAL CULTURE:  The main problem that must be answer is how is the Education Quality Improvement and Development  of Global Culture?  The author  examined  the point of the study related to the education to understand the effort to prepare the learner; improving the quality of education through teaching, guidance and training with basic cultural education institution or  formal  education  in  in  the  era  of  globalization; and the  development  of global  culture.  This  article  found that the education will fulfill the kids and adults using cultural background to understand the changing happened. They must be able to choose the information  and interpret  and place the things happened in the global culture perspective.  In the other side, we have given the big knowledge, but in the other side, we remove and ignore  the  value  of attitudes and behavior,  cognitive,  and affective  and psychomotor  aspects.  The effect  of globalization makes us aware that the global culture may be removed the self- identity  and the culture identity.  In fact, both identities  are the milestones to contribute  the development of global culture.